백색광 소자 응용을 위한 Gd₂WO₆:RE3+ (RE = Dy, Sm, Dy/Sm) 형광체의 구조 및 발광 특성 - 박기원(Giwon Park); 정재용(Jaeyong Jung); 조신호(Shinho Cho) (Biuletyn Uniejowski, 2020)
A series of Dy3+, Sm3+, and Dy3+/Sm3+ doped Gd2WO6 phosphors were synthesized by the conventional solid-state reaction. The X-ray diffraction patterns revealed that all of the diffraction peaks could be attributed to the monoclinic Gd2WO6 crystal structure, irrespective of the type and the concentration of activator ions. The photoluminescence (PL) excitation spectra of Dy3+-doped Gd2WO6 phosphors contained an intense charge transfer band centered at 302 nm in the range of 240–340 nm and two weak peaks at 351 and 386 nm. Under an excitation wavelength of 302 nm, the PL emission spectra consisted of two strong blue and yellow bands centered at 482 nm and 577 nm. The PL emission spectra of the Sm3+-doped Gd2WO6 phosphors had a series of three peaks centered at 568 nm, 613 nm, and 649 nm, corresponding to the 6G5/2→6H5/2, 6G5/2→6H9/2, and 6G5/2→6H11/2 transitions of Sm3+, respectively. The PL emission spectra of the Dy3+- and Sm3+-codoped Gd2WO6 phosphors showed the blue and yellow emission lines originating from the 4F9/2→6H15/2 and 4F9/2→6H13/2 transitions of Dy3+ and reddish-orange and red emission bands due to the 4G5/2→6H7/2 and 4G5/2→6H9/2 transitions of Sm3+. As the concentration of Sm3+ increased from 1 to 15 mol%, the intensities of two PL spectra emitted by the Dy3+ ions gradually decreased, while those of the three emission bands due to the Sm3+ ions slowly increased, thus producing the color change from white to orange. The CIE color coordinates of Gd2WO6:5 mol% Dy3+, 1 mol% Sm3+ phosphors were (0.406, 0.407), which was located in the warm white light region. KCI Citation Count: 0